Experimental investigation of shock wave propagation in the postfocal region of a focussed sound field - HOBAEK, H. (Archives of Acoustics, 1996)
This paper reports some experimental results on the postfocal region of the sound field from a curved circular transducer at very high amplitude. It is found that along the axis the shock front seems to propagate with a speed different from the "background sound". This is explained by diffraction: The field may be separated into two main contributions, one from the edge of the source - arriving first and causing the "background sound" - and one from the main region of the source - causing the shock. After being formed the shock propagates with no change in shape, and with uniformly decreasing amplitude. The shock propagation speed seems to increase slightly with source amplitude.